IDENTIFIKASI POTENSI INTERAKSI OBAT PADA PASIEN RAWAT INAP PENYAKIT DALAM DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO DENGAN METODE OBSERVASIONAL RETROSPEKTIF PERIODE NOVEMBER 2009-JANUARI 2010 - Andriana Sari; Djoko Wahyono; Budi Raharjo (Pharmaciana, 2012)
The potensial drug interaction is potential action of a drug that changed orinfluced by other drugs concurrenly. Drug interactions are defined as a phenomenonthat occurs when the pharmacokinetic effect of a drug changes due to other drugdelivery. Drug interactions could cause advers drug reactions when the potential for apreviously unknown interaction. The purpose of this study is to identify potential druginteractions in patient hospitalized in the Prof. Dr. Margono Soekarjo PurwokertoHospital. The research method was an observasional retrospective study (November2009-January 2010) by using descriptive methods for the data analysis.The resultshowed that the potential drug interactions in the hospitalized patients in Prof. Dr.Margono Soekarjo Hospital is 56,76% (n= 259). Based on the significance categorieswhich proposed by Tatro (2006): a potential drug interaction with significancecategory 1 in ward patients in prof. Dr. Margono Soekarjo Hospital is 16,67%. Thedrug used thet known potential interaction, especially in the category of significance 1should be tailored to the patient’s need, risk and benefit, and have made efforts tooptimize it.